Antecedents of internal crisis communication and its consequences on employee performance - Adamu, Adamu Abbas; Mohamad, Bahtiar; Abdul Rahman, Nik Adzrieman (2016)
This article is taking a conceptual approach to establish the relationship between organizational culture, leadership and social media content on internal crisis communication its consequences on employee performance.The concept of internal crisis communication is relatively new, therefore this article will explore the stage of development of the construct and its contrast with other related concepts.Moreover, Complexity Theory will underpin the study to understand the consequences of minor signals that trigger Internal Crisis Communication. The paper finally offered a framework to guide public relations practitioners on the implications of Internal Crisis Communication on employee performance.